Selections from Galpaguchchha Vol 2 : Manihara and other stories - Rabindranath Tagore; Chattopadhyay Ratan K Tr (Hyderabad Orient Blackswan, 2010)
This three volume English translation by Ratan Kumar Chattopadhyay called Selections from Galpaguchchha is a collection of sixty-one of Tagores short stories broadly grouped under the themes of parting of ways, the relationship between men and women and the power within the woman, respectively. In Volume 2, we find the ever popular Ramkanais Folly, The Ghats Story, Woman Bereft of Jewels, Grandfather and The Matronly Boy, among other stories. The travails of a timid man of indomitable honesty who attains a tragic heroism are narrated in Ramkanais Folly, while the theme of The Ghats Story is the unstated, forbidden love of a young woman for a hermit who may or may not be her long-lost husband. The frisson in the haunting climax of the Woman Bereft of Jewels, a horrifying morality tale of egotism and greed, is justly famous.
Keywords: Indian English Fiction; Indian English Literature